Temperature effects to electrical characterization of N-mosfet using pspice simulator /cChung Yen Ting - 333880 Chung, Yen Ting; Hazri Bakhtiar; Fakulti Sains (2006)
Project Paper (Sarjana Muda Sains dan Komputer serta Pendidikan (Fizik)) - Universiti Teknologi Malaysia, 2006